Xanthogranulomatous prostatitis: A rare mimicker of prostate adenocarcinoma. Issue 1 (13th December 2019) - Mukendi, Alain Mwamba; Doherty, Sean; Mohanlal, Reena
Abstract: Xanthogranulomatous prostatitis as mimicker of prostate adenocarcinoma can cause a diagnostic dilemma, as presented in this case. Therefore, alongside histopathology analysis, multiparametric magnetic resonance imaging (mpMRI) would be useful in this situation by identifying and characterizing suspicious prostatic lesions before biopsy thereby supporting current recommendations on the use of mpMRI. Abstract : Xanthogranulomatous prostatitis as mimicker of prostate adenocarcinoma can cause a diagnostic dilemma, as presented in this case. Therefore, alongside histopathology analysis, multiparametric magnetic resonance imaging (mpMRI) would be useful in this situation by identifying and characterizing suspicious prostatic lesions before biopsy thereby supporting current recommendations on the use of mpMRI.